HANU BASTI AN INNOVATIVE PROCEDURE IN HANU SANDHIGATA ROGA - R. Hiremath, Veerayya; Prasad, B. Srinivasa; Patil, Vasant (International Journal of Ayurveda and Pharma Research, 2018)
Osteoarthritis, a form of arthritis is characterised by chronic degeneration of various hard and soft tissues around the joint. It can also affect the Temperomandibular joint and called as TMJ osteoarthritis. The non dental causes of oral pain closely related to Temperomandibular disorder. It affects both sexes with higher prevalance in women. Hanubasti a form of Bahya Sneha and Sveda, designed on the principle of Shirobasti. Here the word innovative is used because the SOP (standard operating procedure) of Hanubasti is unique and new. We have standardized the procedure and want to conduct large trial of the same. In this article, an attempt is made to describe the methods, indications and precautions of Hanubasti procedure based on the clinical experience and evidence based medicine (EBM).